Sustaining conservation values in selectively logged tropical forests: the attained and the attainable - Putz, F.E.; Zuidema, Pieter A.; Synnott, T; Peña-Claros, M; Pinard, M.A; Sheil, D.; Vanclay, J.K.; Sist, P.; Gourlet-Fleury, S.; Griscom, B; Palmer, J; Zagt, R. (Wiley, 2012)
Most tropical forests outside protected areas have been or will be selectively logged so it is essential to maximize the conservation values of partially harvested areas. Here we examine the extent to which these forests sustain timber production, retain species, and conserve carbon stocks. We then describe some improvements in tropical forestry and how their implementation can be promoted. A simple meta‐analysis based on >100 publications revealed substantial variability but that: timber yields decline by about 46% after the first harvest but are subsequently sustained at that level; 76% of carbon is retained in once‐logged forests; and, 85–100% of species of mammals, birds, invertebrates, and plants remain after logging. Timber stocks will not regain primary‐forest levels within current harvest cycles, but yields increase if collateral damage is reduced and silvicultural treatments are applied. Given that selectively logged forests retain substantial biodiversity, carbon, and timber stocks, this “middle way” between deforestation and total protection deserves more attention from researchers, conservation organizations, and policy‐makers. Improvements in forest management are now likely if synergies are enhanced among initiatives to retain forest carbon stocks (REDD+), assure the legality of forest products, certify responsible management, and devolve control over forests to empowered local communities.